Earworms and Hallucinations - V. Seeman, Mary (Journal of Schizophrenia Disorders And Therapy, 2016)
Background: There is a growing scientific interest in the phenomenon of earworms, which are melodies that are heard and re-heard despite the absence of an external stimulus. Aim: The aim of this paper is to determine whether understanding earworms can shed light on mechanisms underlying auditory hallucinations in psychosis. Method: Using recent data sources, this report briefly reviews what is most relevant about musical hallucinations and earworms. Results: Musical hallucinations, like hallucinated voices, are more prevalent in women. In the elderly, they are often associated with hearing impairment. They are most distressing when they first begin, with the degree of distress inversely proportional to the extent to which they can be controlled. Earworms can be provoked both by the memory of past events and by the anticipation of future events. Strong emotion can trigger earworms, but so can boredom. Limitations: The neurobiology potentially involved in the phenomenon of earworms is not explored in this paper. The pertinence of the literature about earworms and musical hallucinations, while interesting, is of unproven relevance to pathological voices in psychotic illness. Conclusions: The clinical relevance, while unproven, is that addressing recurring memories, as well as managing strong emotions and avoiding occupations that lead to boredom are all strategies worth trying when treating pathologicalauditory hallucinations
Keywords: Earworms; Voices; Musical Hallucinations; Autobiographical Memory; Schizophrenia